(untitled) (Journal of Libya for geographical studies, 2025)
This study examines the challenges facing the urban fabric of the old city of Oujda, focusing on the various factors contributing to the deterioration of its historical buildings. It highlights how natural factors such as geology and climate interact with human factors like urban expansion and population growth, thereby complicating the city’s urban landscape. The study also sheds light on deficiencies in infrastructure and maintenance, changes in land use, and the impact of modern construction on the historical character of the city. In light of these challenges, the study proposes a set of recommendations aimed at mitigating the deterioration of the urban fabric and promoting its sustainability.